Structured trade and commodity finance in emerging markets : what can go wrong and how to avoid it - MacNamara, John, 1960 January 20- (Woodhead, 2001)
John MacNamara's timely report looks at the principles and practice of structured trade and commodity finance deals and what can go wrong. It is supported by invaluable case study material. An authoritative guide to structured trade and commodity finance in emerging marketsA detailed study of the problems and opportunities presented by structured tradeA clear explanation of typical structures and risk mitigation techniques.